2000
DOI: 10.1054/jhsb.2000.0504
|View full text |Cite
|
Sign up to set email alerts
|

Ganglia: The Patient’s Perception

Abstract: This study investigates the concerns of 50 patients with ganglia and their reasons for primary care consultation and referral to a hand unit. Although a minority of patients sought advice and treatment because of pain, more (38%) were concerned about the cosmetic appearance and a significant number (28%) were concerned that their ganglion was a malignant growth. The general practitioners referred 70% of patients to the hand clinic for "excision of the ganglion" and 30% for further "advice and treatment". Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 6 publications
3
50
0
3
Order By: Relevance
“…Volar ganglia may also cause paraesthesia from compression of the ulnar or median nerves or their branches. 9,19 Patients seek treatment when these ganglions become associated with pain, weakness, interference with activities, and an increase in size. 9 The cause of pain is unknown but, in the case of dorsal ganglia, it has been postulated to be from compression of the terminal branches of the posterior interosseus nerve.…”
Section: Clinical Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Volar ganglia may also cause paraesthesia from compression of the ulnar or median nerves or their branches. 9,19 Patients seek treatment when these ganglions become associated with pain, weakness, interference with activities, and an increase in size. 9 The cause of pain is unknown but, in the case of dorsal ganglia, it has been postulated to be from compression of the terminal branches of the posterior interosseus nerve.…”
Section: Clinical Featurementioning
confidence: 99%
“…19 In a study of 55 patients who underwent arthroscopic resection for dorsal wrist ganglion cysts, Edwards and Johansen found that patients had a significant increase in function and a significant decrease in pain within 6 weeks after the procedure. 39 At 2 years after surgery, all patients had wrist motion that was within 5 of preoperative motion; there were no recurrences.…”
Section: 24mentioning
confidence: 99%
“…Recurrence rate after hyaluronidase sclerotherapy is reported to be approximately 25 % [9]. Triamcinolone, when injected in the cyst cavity, lies in close contact with mucin-secreting mesenchymal cells of the cyst lining, arresting the secretion of gelatinous fluid into the cavity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ganglia, while not life-threatening, are cosmetically unacceptable to a significant number of patients, and may cause pain and discomfort (1). There are several management options resulting in varying degrees of success.…”
Section: Discussionmentioning
confidence: 99%